Evolution of Key Factors Influencing Performance Across Phases in Junior Short Sprints - Kyosuke Oku; Yoshihiro Kai; Hitoshi Koda; Megumi Gonno; Maki Tanaka; Tomoyuki Matsui; Yuya Watanabe; Toru Morihara; Noriyuki Kida (Sports)
Sprint performance plays a crucial role in various sports. Short sprints vary depending on the size of the court/playing field and on competitive characteristics, but are common in many sports. Although the relationship between age and muscle strength has been explored in short sprints, there is limited understanding of how various physical factors interact, particularly concerning differences in the acceleration phase. This study examined the relationship between sprint times at 0–2.5 m, 2.5–5 m, and 5–10 m intervals and various factors (body composition, flexibility, muscle strength, physical fitness) in junior athletes (13 boys; 13 girls; average age 11.37 ± 1.30 years; 7 in badminton, 8 in fencing, 5 in rowing, and 6 in climbing). The sprint time was measured using four timing lights at 0 m (start point), 2.5 m, 5 m, and 10 m (finish point). The results indicated that sprint times increased with age, and is correlated with muscle strength and flexibility. A partial correlation analysis showed that faster times in the 0–2.5 m interval were associated with higher hip flexibility (right: r = −0.42, p = 0.035; left: r = −0.60, p = 0.001); in the 2.5–5 m interval, faster times were associated with higher core flexibility (right: r = −0.34, p = 0.091; left: r = −0.40, p = 0.046); and in the 5–10 m interval, a relationship with standing long jump performance was confirmed (r = −0.56, p = 0.003). Furthermore, a lower fat-free body weight translated to higher performance (0–2.5 m: r = 0.40, p = 0.047; 2.5 m: r = 0.37, p = 0.071; 5–10 m: r = 0.55, p = 0.004). In the acceleration phase of 10 m, flexibility immediately after the start and the subsequent horizontal propulsive force are important factors that are strongly related to performance change in each interval. These results emphasize that even over a short distance such as 10 m, the factors influencing performance can change significantly. This highlights the importance of overall flexibility, propulsive power and body fat regulation in junior short sprinters, as well as the need for daily training carefully tailored to the specific sprint distances required in each sport.